2020
DOI: 10.1093/ckj/sfaa130
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney disease and long-term outcomes in critically ill acute kidney injury patients with sepsis: a cohort analysis

Abstract: Background Acute kidney injury (AKI) is frequent during hospitalization and may contribute to adverse short- and long-term consequences. Acute kidney disease (AKD) reflects the continuing pathological processes and adverse events developing after AKI. We aimed to evaluate the association of AKD, long-term adverse renal function and mortality in a cohort of patients with sepsis. Methods We performed a retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
1
24
0
2
Order By: Relevance
“…Xiao et al [ 39 ] also demonstrated AKD was independently associated with increased 90-day mortality in hospitalized AKI patients. Gameiro et al [ 40 ] reported that AKD after AKI was independently associated with the risk of long-term need for dialysis and/or renal function decline and with the risk of death after hospital discharge in a population of 256 septic AKI patients admitted to an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al [ 39 ] also demonstrated AKD was independently associated with increased 90-day mortality in hospitalized AKI patients. Gameiro et al [ 40 ] reported that AKD after AKI was independently associated with the risk of long-term need for dialysis and/or renal function decline and with the risk of death after hospital discharge in a population of 256 septic AKI patients admitted to an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Joana et al conducted a retrospective cohort study of 256 critically ill patients with sepsisassociated AKI to evaluate their risk of adverse renal outcomes after surviving sepsis. Post-discharge 30-day and long-term mortality rates were 21.4% and 44.1%, respectively, whereas the percentage of patients requiring long-term dialysis was 16.5% during followup [24]. Moreover, Hallie et al indicated that survivors of severe sepsis had a higher re-hospitalization rate of 42.7% for sepsis relapse and AKI compared with comorbiditymatched patients without sepsis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Department of military health statistics, Naval Medical University, shanghai, China 2 Department of Clinical Pharmacy, Shanghai General Hospital, School of Medicine, Shanghai Jiaotong University, Shanghai, China.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Acute kidney injury (AKI) could be considered as a severe complication in intensive care unit (ICU), as its association with higher morbidity, higher mortality and poorer outcomes. The incidence of AKI ranges from 2% in the community setting to 20% in hospitalized patients, and even up to 60% in ICU 1 .…”
Section: Introductionmentioning
confidence: 99%